Endoscopic Emergencies in Children - Nascimento, Julie Sarandy; Zaragoza, Simone Santoro Angelo; Ortolan, Erika Veruska Paiva [UNESP]; Lourenção, Pedro Luiz Toledo de Arruda [UNESP]; Bischoff, Andrea (Springer Nature, 2025)
Pediatric digestive endoscopy has undergone great advances during the last decade. As a result, indications have expanded and contraindications have decreased, and emergency endoscopy now has an established role in the diagnosis and treatment of children (Table 91.1).